Application and Evaluation of AHP-ELECTER Performance In The Determination of The Thesis Supervisor - Asslia Johar Latipah (JSE Journal of Science and Engineering, 2020)
Thesis is part of a student's study journey. Universitas Muhammadiyah Kalimantan Timur (UMKT) has a scheme for organizing a thesis that is different from other universities. This Lecturer and Student Collaboration Scheme (KDM) has the concept that thesis work is carried out in groups under the guidance of one lecturer. The role of the supervising lecturer then becomes very important because the determination of the research theme is carried out by the lecturer and students only need to work on the sub-section of the research as their thesis. The selection of supervisors then becomes important and study programs with a very large number of students in one batch as well as study programs with very few students will be overwhelmed by this scheme. The determination of the thesis supervisor is usually done by considering certain criteria. This study uses a combination of AHP and ELECTRE to analyze how the performance of the two methods when faced with the case of determining a supervisor with a different scheme from the thesis in general. The study programs selected as samples were taken from each faculty at UMKT, namely Informatics Study Program, Management Study Program, English Education Study Program, Public Health Study Program and International Relations Study Program. From the five study programs, the most widely used criteria were the functional position of the lecturer, quota, suitability of research with the lecturer roadmap, and student concentration. The results show that AHP-ELECTR can be used to determine supervisors with this KDM scheme with an average accuracy value of 83%. ELECTRE as an alternative removal method is able to eliminate prospective lecturers who do not meet the criteria.